Al-Al'âb Al-Lughawiyyah Bi Istikhdâmi An-Naẓâir Al-Mukhâdi’ah Baina Al-Lugah Al-'Arabiyyah Wa Al-Bâliyyah Fî Mu’jam Ideal Bahasa Bali - Ulul Ilmi; Fajar Sidiq (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
هدف هذا البحث إلى معرفة مفهوم الألعاب اللغوية باستخدام النظائر المخادعة، ومعرفة الألعاب اللغوية المناسبة لتعليم اللغة العربية باستخدام النظائر المخادعة في معجم Kamus Ideal Bahasa Bali للباليين بجامعة الراية، لأن الألعاب اللغوية من أفضل وسائل تعليمية ممتعة فعالة، تستخدم للتعليم عناصر اللغة ومهاراتها. لتحقيق هذا الهدف استخدمت الباحثة منهج الوصفي التحليلي ونوعه البحث الكيفي التجريبي. أجري هذا البحث على 18 عينة من 400 طالبةٍ بجامعة الراية. توصلت الدراسة إلى نتائج تالية: أن الألعاب اللغوية المناسبة لتعليم اللغة العربية للباليين باستخدام النظائر المخادعة في معجم Kamus Ideal Bahasa Bali ظهرت بعد تطبيقها في تعليم اللغة العربية من ناحية مهارة الاستماع. نعرف هذا من نتيجة موافقة الطالبات على أن هذه الألعاب تساعدهن على التفريق بين الحروف العربية المتشابهة عند سماعها وتمييز معنى المفردة بــــــــ68% من جميع عينة البحث. وكذا من نتيجة موافقة الطالبات أن أكثر الألعاب اختيارا واستفادة هي لعبة الأسرار المتسلسلة بعدد 10 طالبات أو 55،5%. The aim of this research was to know the concept of linguistic games using false friends, and to know the appropriate language games for teaching Arabic by using false friends between Arabic and Balinese language in Ideal dictionary of Balinese because linguistic games are one of the most effective and enjoyable teaching methods which used for teaching language elements and their skills. To achieve this goal, the researcher used the descriptive-analytical method and experimental qualitative approach. This research was conducted a sample consist of 18 from 416 Balinese female students at STIBA Ar-Raayah. The study reached the following results: that linguistic games were suitable for teaching Arabic to the Balinese by using false friends in Ideal dictionary of Balinese which appeared after their application in teaching Arabic in terms of listening skill. We knew this from the result of the female students approval that these games helped them to differentiate between Arabic letters similarity when they heard and distinguished the meaning of the vocabulary by 68% of all research sample. As well as from the result of the approval of the students that the most selective and beneficial games were the game of chain secrets with 10 students or 55.5% of them.